Beyond the WEIRD Paradigm: Toward Inclusive Management Approaches to Burnout and Anxiety - Arham, Abd. Basith; Sari, Ika Novita; Abd. Hamid Cholili (Mudir: Jurnal Manajemen Pendidikan, 2026)
The phenomena of burnout and anxiety have become a serious concern in global mental health due to their impact on individual psychological well-being and productivity. Although research on work stress continues to grow, the literature remains largely dominated by Western perspectives, leaving sociocultural aspects in non-Western populations understudied. This systematic review aims to examine how sociocultural factors influence the prevalence, manifestations, and coping strategies for burnout and anxiety in adolescents and adults across various professions. This study followed PRISMA guidelines and searched the Scopus database through 2025. A total of 103 primary studies were selected after a screening process and methodological quality evaluation using the Joanna Briggs Institute (JBI) instrument. The analysis was conducted using narrative thematic analysis and supported by bibliometric mapping using VOS viewer software. The results indicate that cultural context plays a role in shaping experiences of burnout and anxiety. Several studies in collectivistic societies reported more frequent somatization symptoms, while studies in more individualistic societies tended to show a predominance of emotional exhaustion. Furthermore, this study found a predominance of WEIRD (Western, Educated, Industrialized, Rich, and Democratic) samples in the mental health literature, indicating a limited representation of non-Western cultures. Factors such as social stigma, hierarchical structures, and demands for self-sacrifice were associated with an increased risk of burnout, particularly in caregiving professions. Conversely, communal support and spirituality were reported as adaptive coping strategies in various Eastern cultural contexts. These findings underscore the importance of developing more culturally sensitive mental health interventions and organizational policies. However, the results of this study should be interpreted with caution, as the heterogeneity of cultural characteristics and study designs analyzed may limit the generalizability of the findings. Therefore, further research with a more diverse cross-cultural approach is needed to strengthen our understanding of burnout and anxiety in a global context.